The Reproductive Morphology and Physiological Age Grading of the Female Salvinia Weevil, Cyrtobagous salviniae Calder and Sands. (16th May 2018) - Eisenberg, Lee; Johnson, Seth; Grodowitz, Michael J
The morphology of the female Cyrtobagous salviniae Calder and Sands reproductive system is similar to other weevil species being meroistic and telotrophic. The reproductive system is composed of 2 ovaries each containing 2 ovarioles where the follicles mature. A physiological age grading system was developed where the continuum of ovarium development was divided into 2 nulliparous and 3 parous classes. This was based on the differentiation of the ovarioles, presence, and appearance of follicular relics, cuticle hardness/coloration, and fat body quantity/appearance. High correlation occurred between the parous classes and number of eggs produced where the P3 class had over 9-fold higher number of eggs in comparison with the P1 class. Mean number of eggs produced for each parous class was significantly different, however, overlap occurred. Such a system enables a determination of the past, present, and future reproductive status of field populations and mass-rearing colonies.